PANCASILA AS A NORM IN THE BASIS OF THE INDONESIAN LEGAL SYSTEM - Winda Safina; Uswatun Chasana Rambe; Hani Ananda Maulida (Academic Solution Publisher, 2024)
Pancasila is the foundation of the Indonesian state and is the highest source of law in the Indonesian legal system. As an ideological foundation, Pancasila is a guideline in the formation and implementation of laws and regulations. This is reflected in the 1945 Constitution, which emphasizes that every regulation must be in accordance with the values of Pancasila. The values inPancasila includes Divinity. Humanity, Unity, Democracy, and Social Justice. The five principles are a guide in realizing fair laws and creating social order. In legal regulations, all policies and rules made by the government or other state institutions must be based on the values of Pancasila. If there are regulations that conflict, then the regulations are considered invalid and can be revoked. Thus, Pancasila is not only the moral and ethical foundation of the nation, but also has a legal position as the highest guideline that covers all legal regulations in Indonesia.Pancasila is also referred to as the source of all sources of law, why? because it has received legal legitimacy through MPR Decree Number XX/ MPRS/ 1966 concerning the DPR- GR Memorandum Concerning the Source of Legal Order of the Republic of Indonesia and the Sequence of Legislation of the Republic of Indonesia. After the reformation, the existence of Pancasila was reaffirmed in Law Number 10 of 2004 which was then replaced by Law Number 12 of 2011 concerning Legislation. Pancasila as the source of all sources of law gives meaning that the national legal system must be based on Pancasila